Incorporation of Ortho- and Meta-Tyrosine Into Cellular Proteins Leads to Erythropoietin-Resistance in an Erythroid Cell Line - Esztella Mikolás; Szilárd Kun; Boglárka Laczy; Gergő A. Molnár; Eszter Sélley; Tamás Kőszegi; István Wittmann (Karger Publishers, 2014)
Background/Aims: Erythropoietin-resistance is an unsolved concern in the treatment of renal anaemia. We aimed to investigate the possible role of ortho- and meta-tyrosine - the hydroxyl free radical products of L-phenylalanine - in the development of erythropoietin-resistance. Methods: TF-1 erythroblast cell line was used. Cell concentration was determined on day 1; 2 and 3 by two independent observers simultaneously in Bürker cell counting chambers. Protein concentration was determined with colorimetric method. Para-, ortho- and meta-tyrosine levels were measured using reverse phase-HPLC with fluorescence detection. Using Western blot method activating phosphorylation of STAT5 and ERK1/2 were investigated. Results: We found a time- and concentration-dependent decrease of erythropoietin-induced proliferative activity in case of ortho- and meta-tyrosine treated TF-1 erythroblasts, compared to the para-tyrosine cultured cells. Decreased erythropoietin-response could be regained with a competitive dose of para-tyrosine. Proteins of erythroblasts treated by ortho- or meta-tyrosine had lower para-tyrosine and higher ortho- or meta-tyrosine content. Activating phosphorylation of ERK and STAT5 due to erythropoietin was practically prevented by ortho- or meta-tyrosine treatment. Conclusion: According to this study elevated ortho- and meta-tyrosine content of erythroblasts may lead to the dysfunction of intracellular signaling, resulting in erythropoietin-hyporesponsiveness.